POLA PERTUMBUHAN EKONOMI PERTANIAN DALAM PENGEMBANGAN KAWASAN AGROPOLITAN DI KABUPATEN SEMARANG - Santoso, Wahyu Imam; Ayomi, Nun Maulida Suci (Universitas Muhammadiyah Semarang, 2022)
Agropolitan Area Development is one of the concepts in the development of the agricultural sector in Semarang Regency. This study aims to determine the classification of the agricultural subsector in Semarang Regency with the Klassen Typology approach. Furthermore, this study aims to formulate a strategy for developing the agricultural subsector in the context of developing an agropolitan area in Semarang Regency. The basic method of this research is descriptive method with analytical methods in the form of Klassen Typology . The results showed that the Livestock Subsector was the prime agricultural subsector, the Food Crop Subsector, the Annual Horticulture Crop Subsector and the Annual Horticulture Plant Subsector were potential agricultural subsectors in Semarang Regency. The livestock subsector development strategy in Semarang Regency is done by Increasing the Role of Sub Terminal Agribisnis (STA) as a media for business development and promotion of livestock products, Optimizing the management of livestock sector potential through agro-industry development and by developing livestock product quality through labeling and quality certification of livestock products